In vitro protease cleavage and computer simulations reveal the HIV-1 capsid maturation pathway - Jiying Ning (Nature Portfolio, 2016)
Two competing models—disassembly/reassembly and displacive—have been proposed for how immature spherical HIV virions transform into mature particles with conical cores. Here the authors provide evidence that both disassembly/reassembly and displacive processes occur sequentially during the maturation process.